Hospital Acquired Infection and Legionnaires' Disease - Surani, Salim (IntechOpen, 2020)
More than 10,000 patients are hospitalized every year with Legionnaires' disease in the United States alone. Legionnaires' disease is also an important public health topic as it involves environmental and public issues, as far as its spread and prevention are concerned. With an aging population, increasing number of transplants, increasing use of immunosuppressive medications, and compromised immunity due to multiorgan system disease, Legionnaires' disease is emerging as an important disease.